The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/es505419m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a High Efficiency Cabin Air (HECA) Filtration System for Reducing Particulate Pollutants Inside School Buses

Abstract: An increasing number of studies have reported deleterious health effects of vehicle-emitted particulate matter (PM), including PM2.5 (aerodynamic diameter≤2.5 μm), black carbon (BC), and ultrafine particles (UFPs, diameter≤100 nm). When commuting inside school buses, children are exposed to high level of these pollutants due to emissions from both school bus itself and other on-road vehicles. This study developed an on-board high efficiency cabin air (HECA) filtration system for reducing children's exposure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…With rapid urbanization and industrialization the particulate matter (PM) pollution in air, especially the notorious PM 2.5 , causes growing impact on people's living quality, and it poses serious health threats to the public, fatally interferes with equipment operation, as well as influencing climate and ecosystems [1][2][3]. Moreover, stricter emission limits for fine particle emissions from industrial processes and automotive exhaust have also contributed to the urgent need for high performance filters with high filtration efficiency, low energy cost, and long service life [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With rapid urbanization and industrialization the particulate matter (PM) pollution in air, especially the notorious PM 2.5 , causes growing impact on people's living quality, and it poses serious health threats to the public, fatally interferes with equipment operation, as well as influencing climate and ecosystems [1][2][3]. Moreover, stricter emission limits for fine particle emissions from industrial processes and automotive exhaust have also contributed to the urgent need for high performance filters with high filtration efficiency, low energy cost, and long service life [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The particulate matter (PM) pollution in air, especially the notorious PM 2.5 and its attached biological matter involving bacteria and viruses, causes growing impact on people's living quality, and it poses serious health threats to the public, fatally interferes with equipment operation, as well as influencing climate and ecosystems [1][2][3]. Moreover, increasingly stringent regulations for fine particle emissions have also contributed to the urgent need for high performance filters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that exposure to PM 2.5 (aerodynamic diameter ≤2.5 μm) leads to direct and indirect adverse effects on people’s health status and living, visibility, climate, and ecosystems123. Nowadays, the fibrous filters have been widely used for PM filtration due to their fascinating features, such as relatively energy-efficient, cost-effectiveness, ease of scalable fabrication, changeable filter design, and application universality45.…”
mentioning
confidence: 99%